PENGARUH PEMBERIAN KONSENTRAT DAN HIJAUAN YANG BERBEDA TERHADAP RESPONS FISIOLOGI (SUHU REKTAL, DENYUT JANTUNG DAN FREKUENSI PERNAPASAN) SAPI ACEH : THE EFFECT OF DIFFERENT CONCENTRATE AND FORAGE FEEDING ON THE PHYSIOLOGICAL RESPONSES (RECTAL TEMPERATURE, HEART RATE, AND RESPIRATORY RATE) OF ACEH CATTLE - Kamal, Mustafa; Amran, Muhammad; Suryani, Suryani; Aldi, Aldi (Tropical Animal Science, 2025)
This study aims to determine the effect of different feed ratios between concentrate and forage on the physiological responses of Aceh cattle. The study was conducted from December 20, 2023, to January 17, 2024, in Juli Makmu, Juli Mee Teungoh, Kecamatan Juli, Kabupaten Bireuen. The design used in this study was a Completely Randomized Design (CRD) with 4 treatments and 3 replications. The results of the study indicate that the effect of different concentrate and forage feeding did not significantly differ (P>0.05) on the physiological responses (rectal temperature, heart rate, and respiratory rate) of Aceh cattle. The highest average rectal temperature was observed in treatment D, at 38.63°C, and the lowest average was found in treatment A, at 38.53°C. The highest average heart rate was observed in treatment D, at 72.96 beats/min; the lowest average was found in treatments A, B, and C, at 72.09 beats/min. The highest average respiratory rate was observed in treatment D, at 32.84 breaths/min; the lowest average was found in treatment A, at 32.60 breaths/min. Meanwhile, the highest average environmental temperature was observed in treatment D, at 27.67°C, and the lowest average was found in treatment A, at 27.00°C. The conclusion of the research conducted is that the provision of different concentrates and forages does not significantly affect Aceh cattle's physiological response.